Factors of firm growth: Empirical research on China’s listed small and medium-sized IT firms - Ni, Kaiying (2019)
The paper aims to conduct an empirical analysis using the 2015-2018 data of 155 listed companies in the IT industry on China’s stock board. To approach to such analysis, first of all, the author regards Penrose's theory of corporate growth as the main theoretical basis of this research. Secondly, the specific factors are analysed in detail to judge whether they would affect the development of IT industry companies with the combination of current situation of IT industry. Then, IT companies that are listed in the Chinese stock market are selected as a sample to propose relevant assumptions and build four multiple linear regression models for empirical testing. The test results show that the company's total asset turnover rate, cash flow, employee growth rate and pre-research strength are positively correlated with the growth of IT companies, While the current ratio and the previous growth rate are negatively correlated with the steady growth of IT companies. Finally, based on the results of this research, the author proposes suggestions government policies and capital operation and countermeasures that might solve existing problems.